The SEC's Rejection of SFAS No. 19: Tests of Market Price Reversal. - Collins, Daniel W.; Rozeff, Michael S.; Salatka, William K. (The Accounting Review, 1982)
ABSTRACT: Two essentially opposite accounting policy decisions were the FASB proposal to eliminate full cost (FC) accounting and the SEC proposal 13 months later to allow FC accounting while reserve recognition accounting was developed. The SEC's reversal of the FASB decision provides an opportunity to develop additional evidence concerning the market consequences of accounting policy decisions. The authors test whether the SEC proposal had a significant effect on the valuation of FC firms and whether its pricing effect was opposite to that observed at the time of the FASB proposal. A generalized least-squares procedure that takes account of contemporaneous correlation in abnormal return data is employed. The procedure and tests are completely general and appropriate for investigating the market effects of a variety of accounting policy decisions in which cross-sectional correlation of the data is a problem. Evidence is presented that the FC firms had significantly higher returns in the SEC period than the successful efforts firms. Furthermore, within the FC sample, a negative relationship is found between the abnormal returns of individual firms at the times of the FASB and SEC proposals.